2013
DOI: 10.1007/s00384-013-1687-8
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation for fecal incontinence and “low anterior resection syndrome” following neoadjuvant therapy for rectal cancer

Abstract: Preliminary results of sacral neuromodulation in patients with fecal incontinence and symptoms of "low anterior resection syndrome" are promising and enrich the therapeutic modalities if conservative management has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 32 publications
2
56
1
2
Order By: Relevance
“…However, not much is known about the effects of sacral neuromodulation in patients with previous anorectal surgery. In his recent study, Schwandner showed that sacral neuromodulation greatly improved symptoms in nine patients with low anterior resection syndrome after rectal resection and radiotherapy for rectal cancer [21]. Despite the fact that a loss in effectiveness of approximately 10 per cent is demonstrated within 5 years, sacral neuromodulation still remains an effective long-term treatment option [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, not much is known about the effects of sacral neuromodulation in patients with previous anorectal surgery. In his recent study, Schwandner showed that sacral neuromodulation greatly improved symptoms in nine patients with low anterior resection syndrome after rectal resection and radiotherapy for rectal cancer [21]. Despite the fact that a loss in effectiveness of approximately 10 per cent is demonstrated within 5 years, sacral neuromodulation still remains an effective long-term treatment option [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the experience with sacral neuromodulation in patients with fecal incontinence related to the anterior resection syndrome is still limited [53][54][55][56][57]. However, this minimally invasive therapeutic option been considered as the first choice in surgical treatment when conservative therapies fail [54][55][56].…”
Section: Treatment Of Fecal Incontinencementioning
confidence: 98%
“…However, measuring sexual dysfunction in a sufficiently large crc population, while accounting for various confounding and interacting variables, is a challenging task. A miscellany of interventions to ease bowel dysfunction-such as physical therapy, biofeedback, anal sphincter repair, manipulation of bowel flora with antibiotics, and use of sacral neuromodulation-have been tried, and some seem to deliver benefit, but others do not [80][81][82][83] . However, we could find no reviews that investigated the effectiveness of any such interventions in crc patients or survivors.…”
Section: Alcoholmentioning
confidence: 99%